Development of Bangkalan Biomass Model Project as Community based Integrated Wood Pellet Industry - Pamulasari Suyanto, Diah (FIA UB, 2016)
Indonesia has been promoting biomass energy development to improve its energy security effort. One of its strategies is promoting small scaled community based wood pellet industry (WPI). This research used qualitative design and aims to study the development of Bangkalan Biomass Model Project (BMP), a case of community based WPI which combinesthe issues of critical land rehabilitation, carbon sequestration, community development, and enhancement of local community’s socio-economic condition. This research discuss about signsin project impacts, how its secure the partnership among involved stakeholders, and its supporting and constraint factors. Result show that Bangkalan BMP does shows adequately good sign on to critical land rehabilitation effort in Geger Sub Distric, Bangkalan although in small numbers. The partnership among involved stakeholders is found to be not effective due to local government’s lack of participation and support. Project’s multi-benefits and integrated concept and high social capital of geger bangkalan local community have identified as Bangkalan BMP’s supporting factors while lack of finance, ineffective partnership, and under-developed wood pellet local market have been identified as project’s constraint factors.